Penyuluhan Narkoba Dan Bahaya Merokok - Sri Rezeki; Erin Padilla Siregar; Amelia Erawaty Siregar (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
Introduction: Cases of drug abuse and smoking are increasing rapidly in Indonesia, even though the government and society have made various efforts. Drug and cigarette abuse is difficult to eradicate. What can be done is to prevent and control it so that the problem does not spread, thereby harming the future of the nation, due to the decline in the quality of human resources, especially the younger generation. Method: counseling, pre-test and post-test on targets are carried out orally. Results: Participants in this activity were 61 teenagers in Sumber Rejo village. Conclusion: From the pre-test results, the target generally does not know enough about reproductive health regarding the dangers of drugs and smoking. After carrying out verbal post-test counseling, teenagers generally know and have increased abilities on how to maintain reproductive health. This community service has been carried out from August-September 2023, for exactly 3 months